2018
DOI: 10.1029/2018je005744
|View full text |Cite
|
Sign up to set email alerts
|

Compositional Variations in the Vicinity of the Lunar Crust‐Mantle Interface From Moon Mineralogy Mapper Data

Abstract: Moon Mineralogy Mapper spectroscopic data were used to investigate the mineralogy of a selection of impact craters' central peaks or peak rings, in order to characterize the lunar crust‐mantle interface, and assess its lateral and vertical heterogeneity. The depth of origin of the craters' central peaks or peak rings was calculated using empirical equations, and compared to Gravity Recovery and Interior Laboratory crustal thickness models to select craters tapping within +10/−20 km of the crust‐mantle interfac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 65 publications
2
11
0
Order By: Relevance
“…The implications of the presence of ilmenite and quartz were already discussed in Lin et al (2017b). HCP has been observed by remote sensing in lunar craters with diameters larger than~40 km (e.g., Yamamoto et al 2015;Martinot et al 2018aMartinot et al , 2018b), suggesting its presence in the shallow lunar crust. The presence of HCP Fig.…”
Section: Comparison With a Nominally Dry Moonmentioning
confidence: 88%
See 1 more Smart Citation
“…The implications of the presence of ilmenite and quartz were already discussed in Lin et al (2017b). HCP has been observed by remote sensing in lunar craters with diameters larger than~40 km (e.g., Yamamoto et al 2015;Martinot et al 2018aMartinot et al , 2018b), suggesting its presence in the shallow lunar crust. The presence of HCP Fig.…”
Section: Comparison With a Nominally Dry Moonmentioning
confidence: 88%
“…; Martinot et al. 2018a, 2018b), suggesting its presence in the shallow lunar crust. The presence of HCP is generally not linked to primary LMO crystallization processes, but Charlier et al.…”
Section: Discussionmentioning
confidence: 98%
“…Although the olivine has been observed around the Crisium and Moscoviense basins (Yamamoto et al, ), which may have penetrated through the lunar crust (Miljkovic et al, ; Wieczorek et al, ), the exposures of olivine is thought to originate most likely from the lower crust (Head & Wilson, ; Pieters et al, ). As the distribution of olivine can be assumed to be heterogeneous laterally and vertically within the lower crust (Martinot, ), it cannot be the dominated material of upper mantle of the Moon.…”
Section: Discussionmentioning
confidence: 99%
“…One would expect a sample that originated in the mantle to contain little to no plagioclase and be rich in early‐crystallizing minerals. By contrast, mafic compositions with higher relative abundances of plagioclase would more likely originate from a crustal source (Arnold et al, 2016; Martinot et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Olivine is rare on the lunar surface and tends to be associated with larger (>300 km diameter) impact basins (Martinot et al, 2018; Melosh et al, 2017; Miljković et al, 2015; Yamamoto et al, 2010). Using visible (VIS)‐near‐infrared (NIR) data from the Spectral Profiler (SP) on SELENE/Kaguya, Yamamoto et al (2010) reported olivine exposures at six sites around the Imbrium Basin and interpret this material to have originated in the mantle.…”
Section: Introductionmentioning
confidence: 99%